2003
DOI: 10.1002/cm.10136
|View full text |Cite
|
Sign up to set email alerts
|

The ATP‐dependent helicase RUVBL1/TIP49a associates with tubulin during mitosis

Abstract: RUVBL1/TIP49a/Pontin52 is a recently identified multi-functional protein with 2 ATP binding (WALKER) sites, which is essential for cell proliferation. We recovered and identified RUVBL1/TIP49a as a tubulin-binding protein from Triton X-100 lysates of U937 promonocytic cells by protein affinity chromatography and tryptic peptide microsequencing. Performing co-immunoprecipitation using newly generated RUVBL1/TIP49a-specific antibodies (mAb and rabbit polyclonal Ab) and RUVBL1/TIP49a-GST fusion protein-pull down … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
72
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 43 publications
10
72
0
1
Order By: Relevance
“…Taken together, these data suggest a new role for cohesin following sister chromatid cohesion establishment. Interestingly, another ATP-dependent DNA helicase, RUVBL1/TIP49a, was reported to be concentrated at the centrosomes and associate with mitotic spindles during early stages of mitosis (Gartner et al, 2003). RUVBL1 is essential for cellular division and proliferation (Lim et al, 2000), and it is suggested that this protein plays a role in microtubule organization during mitosis since it directly associates with ␣-and ␥-tubulin and was shown to increase tubulin polymerization when over-expressed in the presence of Paclitaxel, a microtubule stabilizer (Gartner et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these data suggest a new role for cohesin following sister chromatid cohesion establishment. Interestingly, another ATP-dependent DNA helicase, RUVBL1/TIP49a, was reported to be concentrated at the centrosomes and associate with mitotic spindles during early stages of mitosis (Gartner et al, 2003). RUVBL1 is essential for cellular division and proliferation (Lim et al, 2000), and it is suggested that this protein plays a role in microtubule organization during mitosis since it directly associates with ␣-and ␥-tubulin and was shown to increase tubulin polymerization when over-expressed in the presence of Paclitaxel, a microtubule stabilizer (Gartner et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The repertoire of RuvBL1 functions was furthermore extended by observations that RuvBL1 is associated with the mitotic spindle and the centrosomes via interactions with tubulin (19). These results suggest that RuvBL1 may play an important role in mitosis.…”
mentioning
confidence: 82%
“…Immunofluorescence Microscopy-Immunofluorescence microscopy was performed as described previously (21). After deparaffinization, sections were incubated with a mixture of CLU H-330 rabbit polyclonal antibody (1:50 dilution) and monoclonal mouse anti-human CgA antibody (1:10 dilution).…”
Section: Methodsmentioning
confidence: 99%